Fatigue study on crack-Inclusion interactions in aerospace engineering materials - Tay, Kian Wei (Nanyang Technological University, 2021)
The aim of this project will be on the elastic-plastic stress study on crack-inclusion interaction in aerospace engineering materials (structures). To analysis failure and various prevention of aerospace engineering materials and structures, the advanced finite element method (XFEM) has been widely used to simulate random cracks. In this project, a model is created to simulate the propagation of a crack in aerospace engineering materials. To analyze the material properties selected for this report, the crack propagation path, the propagation of the crack in the inclusion region will be simulated and analyzed.